2005
DOI: 10.1017/s1431927605050440
|View full text |Cite
|
Sign up to set email alerts
|

Cross Talk between Cell–Cell and Cell–Matrix Adhesion Signaling Pathways during Heart Organogenesis: Implications for Cardiac Birth Defects

Abstract: The anterior-posterior and dorsal-ventral progression of heart organogenesis is well illustrated by the patterning and activity of two members of different families of cell adhesion molecules: the calcium-dependent cadherins, specifically N-cadherin, and the extracellular matrix glycoproteins, fibronectin. N-cadherin by its binding to the intracellular molecule beta-catenin and fibronectin by its binding to integrins at focal adhesion sites, are involved in regulation of gene expression by their association wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…In addition, Smy1p, a kinesin-11 member in Saccharomyces cerevisiae, induces a conformational change in the class V myosin Myo2p, which enhances its interaction with actin and causes cell protrusion in one direction (25,26). Moreover, NMHC II-actin complexes appear to facilitate cross-talk between N-cadherin and integrins during cardiac development (27,28). Therefore, we speculate that Kif26b may enhance the interaction of NMHC II and actin, thereby stabilizing the cell-cell adhesion of mesenchymal cells and the interaction between the mesenchyme and ureteric buds through integrins in the developing kidney.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Smy1p, a kinesin-11 member in Saccharomyces cerevisiae, induces a conformational change in the class V myosin Myo2p, which enhances its interaction with actin and causes cell protrusion in one direction (25,26). Moreover, NMHC II-actin complexes appear to facilitate cross-talk between N-cadherin and integrins during cardiac development (27,28). Therefore, we speculate that Kif26b may enhance the interaction of NMHC II and actin, thereby stabilizing the cell-cell adhesion of mesenchymal cells and the interaction between the mesenchyme and ureteric buds through integrins in the developing kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a member of a the Caϩϩ-dependent family of adhesion molecules, N-cadherin, is responsible for the connection of actin and myofibrils between neighboring myocytes at cell-cell junctions (Linask, 1992a;Kostetskii et al, 2005) and for the cell alignment and arrangement of the two layers of the developing heart tube (Shiraishi et al, 1993). Thus, during looping, as in the earlier period of cardiac compartment formation, cross-talk between two adhesion mediated-signaling pathways, integrin and N-cadherin, is evident (Linask and Lash, 1990;Linask, 1992b;Linask et al, 2005b) and as shown here, appears to be facilitated by the actinnonmuscle myosin-II complex.…”
Section: Actomyosin Cytoskeleton and Heart Loopingmentioning
confidence: 99%
“…This class of proteins is integral to actomyosin interactions, to cilia and involved with mechanotransduction and is a seemingly logical protein complex to be involved in heart tube bending. The well recognized intracellular cross-talk between cell-cell adhesion and cell-matrix interactions to coordinate development of form and function (Linask et al, 2005b) suggested that proteins associated with the cytoskeleton facilitate heart looping.…”
Section: Introductionmentioning
confidence: 99%
“…In organ formation, cell fate is regulated by a combination of cell-specific genes that control intracellular events and responses to the environment, such as cell-cell and extracellular matrix-mediated interactions (4). To understand the mechanisms of differentiation through ES cells in detail, Kaede proteins may have the advantage of statically tracing the positions of living cells of interest.…”
Section: Introductionmentioning
confidence: 99%